2015
DOI: 10.1007/s00402-015-2189-7
|View full text |Cite
|
Sign up to set email alerts
|

One step closer to sparing total blood loss and transfusion rate in total knee arthroplasty: a meta-analysis of different methods of tranexamic acid administration

Abstract: This study showed that TXA leads to significant reductions in TBL and the rate of allogeneic transfusions. Generally, no significant difference was detected between IA and IV administration of TXA; however, more studies with focus on safety and efficacy are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 55 publications
1
35
0
3
Order By: Relevance
“…Topical (intra-articular) and systemic (IV) TXA as the most routinely used single dose regimens have been shown to be safe and effective. 4,5,9,10 Recent RCTs have generally reported that IV and topical regimens had similar efficiency, 1,4,11 whereas a recent study concluded that the topical regimen seemed to be more effective. 6 After many studies evaluating and comparing the single regimens, combined regimens (IV þ topical) started to be investigated with the aim of The values are given as the mean + standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…Topical (intra-articular) and systemic (IV) TXA as the most routinely used single dose regimens have been shown to be safe and effective. 4,5,9,10 Recent RCTs have generally reported that IV and topical regimens had similar efficiency, 1,4,11 whereas a recent study concluded that the topical regimen seemed to be more effective. 6 After many studies evaluating and comparing the single regimens, combined regimens (IV þ topical) started to be investigated with the aim of The values are given as the mean + standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the advances in knowledge of patient blood management, efforts to reduce blood transfusion have improved in clinical practice. In addition, various methods to reduce transfusion have been attempted in hip arthroplasty recently, with a high percentage of patients requiring transfusion during and after the procedures …”
mentioning
confidence: 99%
“…Nevertheless, a study that reviewed TKA and THA patients for six weeks, found that over 90% of all lifethreatening complications occurred within 4 days after surgery [5] . Multiple studies, including randomized controlled trials [6][7][8][9] and meta-analyses [10][11][12][13][14] have found the same promising results on the effectiveness of TXA. In accordance with our research, multiple other studies have been underpowered to detect a difference in VTE rates.…”
Section: Discussionmentioning
confidence: 84%